2020
DOI: 10.20546/ijcmas.2020.906.191
|View full text |Cite
|
Sign up to set email alerts
|

Study on Genetic Effect of Yield and Related Traits through Generation Mean Analysis in Wheat (Triticum aestivum L.)

Abstract: The objective this study was to effect of gene effects for some agronomical traits (plant height, number of effective tillers per plant, number of spikelet per spike, number of seeds per plant, seed yield and biological yield) of Cross I CG1608 (HI 1544 x GW 2013 and Cross II CG 1639 (RAJ 4270 x GW 366) The experimental material comprising of six generations ( P 1 , P 2 , F 1 , F 2 , BC 1 and BC 2 ) of wheat crosses was planted during rabi 2018-19 in randomized block design of two replication under irrigated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The contribution of (d) in the inheritance of DH and DM was also stated by Raza et al [41], Attri et al [42] and Saleem et al [44] for proline content. Moreover, Sultan et al [37], Patel et al [43] and Sharma et al [20] reported additive genes were controlled traits of yield components in the various wheat crosses.…”
Section: Types Of Gene Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution of (d) in the inheritance of DH and DM was also stated by Raza et al [41], Attri et al [42] and Saleem et al [44] for proline content. Moreover, Sultan et al [37], Patel et al [43] and Sharma et al [20] reported additive genes were controlled traits of yield components in the various wheat crosses.…”
Section: Types Of Gene Actionmentioning
confidence: 99%
“…Therefore, heterosis breeding could be possible to the improvement of these traits over hybridization (recombination breeding) followed by selection at later generations to obtain better lines under both good irrigation and drought stress environments and it is suggesting for exploiting dominance gene action (h) and these methods must be followed in the next future study. The various studies exhibited also the complex genetic inheritance of grain yield/plant and its components [20,29,46].…”
Section: Types Of Gene Actionmentioning
confidence: 99%
See 1 more Smart Citation